Uji Pertumbuhan Dan Daya Hasil Enam Genotipe Tomat (Lycopersicum esculentum Mill) di Dataran Rendah - Situmorang, Agus; ', Adiwirman; ', Deviona (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The objective of this study was to test determine six genotypes of tomato plants that can adapt in lowlands. This experiment was conducted at the Technical Services Unit of the Faculty of Agriculture from October 2012– February 2013. The exsperimen userandomized block design with six treatments of tomato genotype: Genotype IPB T34-7-7, Genotype IPB T57-3, Genotype IPB T33-1-3, Genotype IPB 53-3-3, Ratna and Karina with 3 replications. Parameters those measured were stem diameter, plant height, flowering, harvest, fruit length, fruit diameter, flesh thickness, fruit cavity number, weight per fruit, fruit weight per plant and number of seeds per gram. The results showed that of all genotypes tested significantly affect crop growth and yield. Genotypes tested significantly affected flowering, harvest, plant height, fruit length, fruit diameter, flesh thickness, weight per fruit, number of seeds per gram and the total weight of crop and not significantly different to the amount of fruit and stem diameter cavity. Results of total weight per plant was highest in Genotype IPB T33-1-2 and followed Genotype IPB T53-3-3 and the lowest total weight per plant found in Genotype IPB T34-7-7 and followed Genotype IPB T57-3. Keywords: tomato, result, genotypes, lowlands.